Tinjauan Literatur: Perkembangan Teori Akuntansi - Cindy Limtaroli; Venny -; Novita -; Carmel Meiden (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
Findings and opinions build a theory. Almost all fields or research areas certainly have theory as the basis for their practice. This study aims to describe and explain the development of accounting theory and practice, as well as to draw conclusions from previous studies or research. The method used in this study is systematic literature review (SLR) with a selected sample of 30 articles, both from within the country and abroad, published from 2012-2022. Selected articles with similar research topics, namely the discussion of accounting theory, its development and implementation. Until now, research on accounting theory is still often carried out, both carried out by domestic and foreign parties. Accounting theories are also still often used as a reference in research, especially accounting theory itself, positive accounting theory, agency theory, and normative accounting theory.